ESG SCORES, EARNINGS MANAGEMENT AND FINANCIAL PERFORMANCE: EVIDENCE FROM POLAND - Michał Comporek (Фінансово-кредитна діяльність: проблеми теорії та практики)
The paper's main aim is to investigate the relationship between the ESG activities scores and profitability metrics of 33 public companies listed on the Warsaw Stock Exchange. By utilizing the Refinitiv methodology, we answer whether a company's environmental, social and governance performance perspectives positively affect the ROA, ROE and ROC ratios or whether there is a negative relationship. A secondary objective of the research is to investigate the relationship between profitability and the magnitude of aggregate-based earnings management in the tested sample. The moderating effect of earnings manipulation on the links between ESG performance and a company's profitability metrics is a research gap that has not been well-studied to date. This research demonstrates contradictory results: a positive relationship between the social dimension of ESG activities and the financial performance of companies was observed regarding ROE and ROC ratios. The negative impact of the environmental pillar rank on the ROA ratio was captured only in selected regression analyses. The governance pillar score did not statistically affect the tested profitability metrics. On the other hand, we gathered evidence that public companies with a high range of non-financial disclosures tend to alter earnings via accruals, and discretionary accruals statistically affect the ROA, ROE and ROC ratios. This finding contrasts previous research claiming that the earnings management phenomenon is a typical agency problem and that the policy of non-mandatory disclosures following the ESG assumptions could constrain the asymmetry of information and managerial information advantages.